Sleepiness, fatigue, anxiety and depression in Chronic Obstructive Pulmonary Disease and Obstructive Sleep Apnea – Overlap – Syndrome, before and after continuous positive airways pressure therapy - Economou, Nicholas-Tiberio; Ilias, Ioannis; Velentza, Lemonia; Papachatzakis, Yiannis; Zarogoulidis, Paul; Kallianos, Anastasios; Trakada, Georgia (PloS one, 2018)
Patients with Chronic Obstructive Pulmonary Disease (COPD) and / or Obstructive Sleep Apnea (OSA) often complain about sleepiness, fatigue, anxiety and depression. However, common screening questionnaires, like Epworth Sleepiness Scale (ESS), Fatigue Severity Scale (FSS) and Hospital Anxiety and Depression Scale (HADS) have not been previous evaluated in patients with overlap-coexisting COPD and OSA-syndrome versus patients with OSA alone. Our study compared ESS, FSS and HADS between patients with overlap syndrome and patients with OSA, before and after treatment with Continuous Positive Airways Pressure (CPAP). We examined 38 patients with coexisting COPD and OSA versus 38 patients with OSA-only and 28 subjects without respiratory disease, serving as controls. All patients underwent pulmonary function tests (PFTs), oximetry and overnight polysomnography and completed the questionnaires, before and after 3 months of CPAP therapy. The two patient groups did not differ significantly in terms of age, Body Mass Index (BMI), neck, waist and hip circumferences, and arterial blood pressure values. They also had similar comorbidities. They differed significantly, as expected, in PFTs (Forced Vital Capacity-FVC, 2.53±0.73 vs 3.08±0.85 lt, p = 0.005, Forced Expiratory Volume in 1sec-FEV1, 1.78±0.53 vs 2.60±0.73 lt/min, p<0.001) and in daytime oximetry (94.75±2.37 vs 96.13±1.56%, p = 0.007). ESS, HADS-Anxiety and HADS-Depression scores did not differ statistically significant between these two groups, whereas overlap syndrome patients expressed significantly more fatigue (FSS) than OSA-only patients, a finding that persisted even after 3 months of CPAP therapy. We conclude that sleepiness, anxiety and depression were similar in both groups, whereas fatigue was more prominent in patients with overlap syndrome than in sleep apneic patients and did not ameliorate after treatment.